Clinical Applications and Therapeutic Mechanisms of Chinese Herbal Medicine Yiaikang Capsules in Treating Acquired Immune Deficiency Syndrome - Ding X; Fan L; Xu L; Ma X; Meng P; Li J; Yue J (Infection and Drug Resistance, 2025)
Xue Ding,1 Leilei Fan,2 Liran Xu,3 Xiuxia Ma,4 Pengfei Meng,3 Jiahe Li,3 Jingyu Yue4 1Department of Medicine, The First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 2Department of Cardiovascular, The First People’s Hospital of Zhengzhou, Zhengzhou, People’s Republic of China; 3Department of the First Clinical Medical College, Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 4Department of AIDS Clinical Research Center, The First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, People’s Republic of ChinaCorrespondence: Jingyu Yue, Department of AIDS Clinical Research Center, The First Affiliated Hospital of Henan University of Chinese Medicine, 19 Renmin Road, Zhengzhou, People’s Republic of China, Email yuejingyu@aliyun.comAbstract: Yiaikang (YAK) is a 22-component traditional herbal medicine, exhibiting a powerful inhibitory effect on viral replication and immunity-boosting activities in clinical applications, and is widely used to treat diseases in people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) in China. In clinical studies, YAK alleviates the clinical symptoms of HIV/AIDS (eg, weakness, shortness of breath, spontaneous sweating, and diarrhea) while enhancing quality of life and improving survival rates of patients. In the molecular mechanism studies, its main therapeutic action is inhibition of HIV replication, alongside increased numbers of CD4+ T cells. These are achieved through inhibition of the viral transactivator of transcription (Tat) and regulatory protein Rev, and host intercellular adhesion molecule 1 (ICAM-1). During HIV infection, the extensive destruction of CD4+ T cells consumes the Th17 subset of intestinal-associated lymphoid tissue, resulting in the loss of mucosal integrity. YAK also restores the normal expression of C-C chemokine receptor type 5 (CCR5) and C-X-C chemokine receptor type 4 (CXCR4), promotes the proliferation of natural killer cells, regulates the balance between T helper 17 cells and regulatory T cells, and maintains the integrity of the intestinal mucosal barrier. In this review, we describe the clinical applications and therapeutic mechanisms of YAK in treating AIDS, with the goal of identifying new and efficacious therapies targets and approaches and provides new clues for the clinical application of YAK.Keywords: Yiaikang capsule, acquired immune deficiency syndrome, human immunodeficiency virus